Isolation, purification, and partial characterization of Brucella abortus matrix protein. - Moriyon, I (1983)
Peptidoglycan sacculi with peptidoglycan-associated proteins were prepared from cell envelopes of Brucella abortus by extraction with sodium dodecyl sulfate (SDS) at 50 degrees C. On extraction of these preparations with SDS at 100 degrees C, a protein was obtained whose removal from peptidoglycan was confirmed by electron microscopy. Incubation of the 50 degrees C SDS-extracted cell envelopes with 50 mM MgCl2 in SDS-2-beta-mercaptoethanol at 37 degrees C also extracted the protein, along with lipopolysaccharide. At temperatures below 60 degrees C, the protein did not bind SDS strongly and had an apparent molecular weight greater than 92,000 in SDS-polyacrylamide gel electrophoresis. At higher temperatures, SDS bound strongly, and the apparent molecular weight was 38,000. Urea at 5 M did not alter the electrophoretic mobility of this 38,000-molecular-weight form. Immunoelectrophoresis in detergents with antisera to cell envelopes, carbohydrate staining of SDS-polyacrylamide gels, and production of anti-lipopolysaccharide antibodies by mice immunized with the purified protein indicated that lipopolysaccharide was present in free and protein-bound forms. Sequential gel filtration in SDS-EDTA and SDS-NaCl removed most lipopolysaccharide. After further purification by preparative SDS-polyacrylamide gel electrophoresis, a gas-liquid chromatographic analysis showed residual lipid tightly associated with the protein. The results suggested that the interactions between matrix proteins and other outer membrane components are stronger in B. abortus than in Escherichia coli, which was used as a control throughout.